Republic of Moldova : Technical Assistance Report-Country Governance Assessment. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2021)
Despite having legal and institutional frameworks largely in place, Moldova continues to suffer from significant corruption and governance vulnerabilities. These are fairly pronounced in the areas of rule of law, anti-corruption, anti-money laundering and combatting the financing of terrorism (AML/CFT), and SOE governance, while other areas assessed for purposes of this report (PFM, tax administration, central bank governance and financial sector oversight) presented some good progress in mitigating such vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Moldova, Republic of